Factors affecting breastfeeding adherence among Chinese mothers: A multicenter study. Issue 38 (September 2017) - Huang, Pan; Ren, Jianhua; Liu, Yi; Luo, Biru; Zhao, Xiufang
Abstract : Abstract: Breastfeeding is beneficial for both infant and mother, but discontinuation of breastfeeding is very common. To investigate maternal breastfeeding intention and the rate of breastfeeding based on the theory of reasoned action, and analyze the predominant factors associated with breastfeeding and breastfeeding problems. This observational study was conducted in 3 hospitals. Three researchers recruited women at 3 time points in the hospitals: initial documentation of pregnancy at the outpatient department, prenatal admission, and postpartum discharge. SPSS version 21 was used for statistical analyses. Significance was set at P  < .05. In the multivariate analysis, binary logistic regression was used and odds ratios (ORs) with 95% confidence intervals (CI) were calculated. We recruited 1260 women, with 420 pregnant women at each time point. 55.1% of the infants were exclusively breastfed, 40.6% were mixed fed, and 4.3% were formula fed when discharged from hospital. A total of 53.8% of the mothers declared having breastfeeding problems. The multivariate analysis showed that nonsuccessful breastfeeding was associated with neonatal birth length, food intake before breastfeeding, infrequent sucking, the intention of breastfeeding, understanding level of the benefits of breastfeeding and that breastfeeding problems were related with the understanding level of the benefits of breastfeeding, neonatal birth length, normal vaginal delivery, breast size, the experience of breastfeeding, use of pacifier and the needs of family member's support in breastfeeding. Most mothers who intended to practice exclusive breastfeeding initially chose to add formula and had breastfeeding problems when discharged from hospital. Successful breastfeeding depends on antenatal and postnatal breastfeeding education and on support provided by healthcare professionals.